Definition of Barrett Esophagus in the United States: Support for Retention of a Requirement for Goblet Cells. (February 2018) - Salimian, Kevan J.; Waters, Kevin M.; Eze, Ogechukwu; Pezhouh, Maryam K.; Tarabishy, Yaman; Shin, Eun-Ji; Canto, Marcia I.; Voltaggio, Lysandra; Montgomery, Elizabeth A.
Abstract : Barrett esophagus (BE) predisposes patients to the development of esophageal adenocarcinoma (EAC). However, the global definition of BE is controversial. Pathologists in Europe and the United States require intestinal metaplasia (IM) within columnar-lined mucosa (CLM) in the tubular esophagus to diagnose BE, whereas in the UK and Japan only the presence of CLM is required. To aid in establishing an appropriate definition for BE, we evaluated whether IM accompanies EAC in a US patient cohort. We examined a series of 139 consecutive patients who underwent endoscopic mucosal resections or esophagectomies for EAC performed at a US tertiary care center. The resection specimens were evaluated for the presence (IM+) or absence (IM−) of IM within CLM. Ninety-seven (70%) patients were IM+. Tumors found in IM− patients tended to be advanced at the time of resection (57% pT3 or greater, IM−; 31% pT3 or greater, IM+; P =0.02) such that the tumor may have "overgrown" zones of IM. We hypothesized that changes as a result of neoadjuvant chemotherapy or radiation might mask preexisting IM. When evaluating this hypothesis, we found that 34 of 39 of treatment-naive patients were IM+. Two of the 5 IM− patients had prior IM+ biopsies resulting in 92% of treatment-naive patients who were IM+. In our US hospital population, CLM with IM in the tubular esophagus is found in association with EAC in 70% to 92% of patients. We believe that based on these data the United States definition of BE should continue to require the presence of IM.